169k views
4 votes
Simplify (−8b)(−15b).
120b2
−120b2
120b
−120b

2 Answers

3 votes

Answer:


120b^2

Explanation:

When multiplying two terms, multiply the coefficients and the variables.

Also, remember the rules for multiplying integers:

  • negative * positive = negative
  • negative * negative = positive
  • positive * positive = positive

-8 * -15 = +120

b * b =
b^2

∴(-8b)(-15b) =
120b^2

User Try
by
5.7k points
3 votes


(-8b)(-15b)


(-8)* b*(-15)* b


120* b^2


=120b^2


\fbox{Option A}

User Albert Martin
by
5.8k points